1995
DOI: 10.1002/macp.1995.021960710
|View full text |Cite
|
Sign up to set email alerts
|

Interpolymer complexes of (co)poly(vinyl ethers) of glycols and poly(carboxylic acids)

Abstract: The complex formation reaction of poly(viny1 ethers) of ethylene glycol (l), poly(viny1 ether) of diethylene glycol (2), copolymers of vinyl ether of ethylene glycol and vinyl butyl ether (3 a-3 c) with poly(acry1ic acid) (PAA) and poly(methacry1ic acid) (PMAA) was studied by conductimetric, viscometric and spectroturbidimetric methods in aqueous solution. It is shown that 1 and 2 do not form polycomplexes with PAA. While an introduction of hydrophobic vinyl butyl ether fragments into the structure of 1 enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The stability of polycomplexes formed both in aqueous and in organic solutions in respect to the addition of dimethylformamide has been studied. 11) was demonstrated. The possibility of a complex formation of these copolymers with poly(carboxylic acid) in aqueous solutions may be considered from two positions.…”
Section: Communicationmentioning
confidence: 86%
“…The stability of polycomplexes formed both in aqueous and in organic solutions in respect to the addition of dimethylformamide has been studied. 11) was demonstrated. The possibility of a complex formation of these copolymers with poly(carboxylic acid) in aqueous solutions may be considered from two positions.…”
Section: Communicationmentioning
confidence: 86%
“…1). [9,10]. it was shown that poly(vinyl ether) of ethyleneglycol does not form IPC with poly(-carboxylic acids).…”
mentioning
confidence: 98%
“…The kinetics of PEC formation on a dimeric interface was measured and the activation energy of this process was calculated. Copyright [9,10] we studied the complex formation ability of water-soluble copolymers of vinyl ether of ethyleneglycol (1) and butyl vinyl ether with respect to the poly(carboxylic) acids. It has been shown that an introduction of more hydrophobic butyl vinyl ether fragments into the structure of 1 enhances the formation of interpolymer complexes (IPCs).…”
mentioning
confidence: 99%
“…Therefore the decreasing of pH of the solution should be favorable for complex formation. As it was found earlier 8,9) the addition of aqueous solution of poly(vinyl ether) of ethylene glycol to aqueous solution of poly(acrylic acid) in weakly acidic media (pH = 4 q 5) does not lead to the formation of IPC and is accompanied by a marked increase in the intrinsic viscosity. Apparently, this can be attributed to the presence of the polyelectrolyte effect.…”
Section: Resultsmentioning
confidence: 78%
“…Earlier 8,9) we have studied the complex formation between poly(vinyl ethers) of glycols and poly(carboxylic acids). But the formation of a sufficiently stable complex has been proved only for poly(vinyl ether) of diethylene glycol and poly(methacrylic acid).…”
Section: Introductionmentioning
confidence: 99%